Pathogenesis of Brucella suis biovar 1 in the armadillo (Chaetophractus villosus) - Kin, Marta Susana (2024)
Brucella suis biovar 1 has the broadest animal host spectrum. Affects domestic animals and wildlife species. The aim of our study was to investigate the pathogenesis of B. suis biovar 1 infection in the armadillo (Chaetophractus villosus) under experimental conditions. One gravid female and three adult males were inoculated with a suspension containing 1×106 CFU/mL (colony-forming units) of B. suis biovar 1 by oral route. In addition, the gravid female and one male received the same suspension by the conjunctival route. A young male and two females not inoculated were kept in contact with the animals inoculated. The animals that tested seropositive were euthanized. All inoculated armadillos showed positive antibody titres 2 weeks post inoculation. Of the three uninoculated animals, one female was seropositive for Brucella infection. Brucella was isolated from the spleen, liver, mesenteric lymph nodes, uterus, testes, and urine. Characteristic histologic lesions were found in the epididymis. These results suggest that armadillos can act as a reservoir for the spread of B. suis infection, and the persistence of Brucella in armadillo tissues constitutes a risk for humans, because of the cultural practice of armadillo meat consumption in rural communities.